From the DEAL engine room — an interview with Bernhard Mittermaier - Bernhard Mittermaier (Library Ideas, 2017)
For more than a year there is one topic that has kept the German research community in suspense: the DEAL with the three dominating scholarly publishers Elsevier, Springer Nature and Wiley. The hoped-for deal is a Germany-wide contract, which in addition to access to the journal portfolios should also regulate an open access component for publications by German researches. In this interview, Bernhard Mittermaier, representing the DEAL negotiating team, reports on how to plan, organize and carry out such negotiations without being led astray.